Platelet activation status, on-treatment platelet reactivity and reticulated platelets in the early and late phases after TIA/ischaemic stroke - LIM, SOON TJIN (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2020)
Aims: This thesis aimed to assess platelet activation status, on-treatment platelet reactivity and the profile of reticulated platelets in patients with ischaemic cerebrovascular disease (CVD) who were commencing or changing antiplatelet therapy. Methods: We conducted a collaborative systematic review and meta-analysis of relevant published data on Antiplatelet-high on treatment platelet reactivity (Antiplatelet-HTPR) following TIA/ischaemic stroke. We performed independent, observational analytical studies with comprehensive, longitudinal follow-up in eligible adult patients within 4 weeks of TIA/ischaemic stroke onset who were commencing or changing antiplatelet therapy. Patients underwent detailed clinical and laboratory assessment with venepuncture before (baseline), 14 +/- 7 days after (14d), and at least 90 days (90d) after starting aspirin, clopidogrel or after adding dipyridamole to aspirin, with additional clinical follow-up at ≥ 1 year after symptom onset. Platelet activation status was assessed with whole blood flow cytometry to quantify the expression of platelet surface activation markers (CD62P and CD63), circulating leucocyte-platelet complexes, and the percentage of circulating reticulated platelets (%RP). The prevalence of ex vivo high on- treatment platelet reactivity (HTPR) in whole blood was assessed with the PFA-100®, VerifyNow® and Multiplate® platforms. Results: Our meta-analysis suggests that identification of Antiplatelet-HTPR predicts the risk of recurrent vascular events and outcomes in CVD patients, especially on aspirin. 124 patients were assessed at baseline in the longitudinal studies assessing platelet activation and HTPR status in patients commencing aspirin, clopidogrel or dipyridamole. 211 patients were assessed at baseline in the collaborative case-control studies assessing the %RP in patients with recent TIA/stroke. There were no changes in platelet activation status over time in the cohort of patients who commenced aspirin or clopidogrel. The % monocyte-platelet complexes initially increased at 14d, but this increase was not sustained at 90d in the overall cohort of patients who commenced dipyridamole treatment; we confirmed this rise was driven by data from the subgroup of patients with dipyridamole-HTPR. The PFA-100®, VerifyNow® and Multiplate® assays were found to be effective at detecting the ex vivo antiplatelet effects of aspirin, clopidogrel and dipyridamole. The prevalence of Aspirin-HTPR by a 'cross-sectional/case-control definition' across all devices was 9.5 - 23.8% at 14 days and 7.7 - 30% at 90d. The prevalence of aspirin-HTPR by our 'novel longitudinal definition' was 4.8% at 14 days and 7.7% at 90d. The cross-sectional prevalence of Clopidogrel-HTPR was 31.6 - 60.5% overall in the early phase and 20.8 - 56% in the late phase after TIA/ischaemic stroke. The prevalence of Clopidogrel-HTPR with our novel longitudinal definition was lower at 14d (13.9 - 21%) and 90d (4 - 4.5%). The prevalence of Dipyridamole-HTPR with our novel longitudinal definition was 75-83.3% during the early phase and 71.4 - 81.5% during the late phase after TIA/stroke. The %RP was increased in the late phase (> 90 days), but was not significantly increased in the early phase (≤4 weeks) after TIA or ischaemic stroke overall compared with healthy controls. The %RP was significantly elevated only in the subgroup of patients with TIA/stroke due to small vessel disease at baseline and at 90d, but not at 14d vs. controls, with the findings in this small vessel disease subgroup at 14d possibly reflective of a type II error. Conclusions: An important proportion of CVD patients have Antiplatelet-HTPR with 'user-friendly' assays. The prevalence of Aspirin-HTPR and Clopidogrel-HTPR was numerically lower with novel longitudinal vs. cross-sectional definitions. Simultaneous assessment of platelet activation status and reticulated platelets may improve our understanding of the pathogenesis of Antiplatelet-HTPR in CVD. Large, multi-centre studies have been designed to definitively assess whether testing HTPR status can facilitate personalised antiplatelet therapy in CVD patients to optimise secondary prevention following TIA/ischaemic stroke.
APPROVED
Keywords: Platelets; Stroke; TIA; High on Treatment Reactivity